Cardiovascular System. Heart. Aorta. Carotid Artery - Abdurashitovich, Zikrillaev Farrux (Journal of Science in Medicine and Life, 2024)
Heart (Latin: cor, Greek: cardia) is a hollow muscular organ with an irregular conical shape, the heart is the central organ of the blood-vascular system, and it is the organ that performs the function of pumping blood to all organs and tissues in the body. It is located in the middle of the lower chest area. The heart is divided into the following morphological parts: the base (basis) directed upwards and slightly backwards and the tip (apex) directed forward, downward and to the left are distinguished.